2022
DOI: 10.1101/2022.02.03.479017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of Craniofacial Development by the Collagen Receptor, Discoidin Domain Receptor 2

Abstract: Development of the craniofacial skeleton requires interactions between progenitor cells and the collagen-rich extracellular matrix (ECM). The mediators of these interactions are not well-defined. Mutations in discoidin domain receptor 2 (DDR2), a non-integrin collagen receptor, are associated with craniofacial abnormalities, such as midface hypoplasia and open fontanels. However, the exact role of DDR2 in craniofacial morphogenesis is not known. As will be shown, Ddr2-deficient mice exhibit defects in craniofa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…In mice, Ddr2 is expressed in a gradient fashion in the long bone growth plate, with highest levels in the resting zone and lowest in the hypertrophic zone [113]. In the cranial base synchondroses, a similar expression gradient is observed [114]. Lineage tracing using a tamoxifen-inducible Ddr2-creER line showed that Ddr2-labeled cells are present in the cranial sutures and the resting and proliferating zones of the ISS and SOS, which could then differentiate into hypertrophic chondrocytes, osteoblasts and osteocytes, supporting the concept that Ddr2 is expressed by skeletal progenitors.…”
Section: Discoidin Domain Receptors Play Critical Roles In the Organi...mentioning
confidence: 86%
See 1 more Smart Citation
“…In mice, Ddr2 is expressed in a gradient fashion in the long bone growth plate, with highest levels in the resting zone and lowest in the hypertrophic zone [113]. In the cranial base synchondroses, a similar expression gradient is observed [114]. Lineage tracing using a tamoxifen-inducible Ddr2-creER line showed that Ddr2-labeled cells are present in the cranial sutures and the resting and proliferating zones of the ISS and SOS, which could then differentiate into hypertrophic chondrocytes, osteoblasts and osteocytes, supporting the concept that Ddr2 is expressed by skeletal progenitors.…”
Section: Discoidin Domain Receptors Play Critical Roles In the Organi...mentioning
confidence: 86%
“…Ddr2-deficient mice display craniofacial abnormalities, including significant reductions in the lengths of the anterior and posterior cranial base and reduced mineralization of the frontal suture. Defects in cranial base length were related to reduced proliferation in both ISS and SOS chondrocytes in the absence of altered apoptosis or reduced osteoblast differentiation [ 114 ]. Interestingly, the reduced cranial base growth was associated with widening of synchondroses, loss of chondrocyte polarity and abnormal distribution of ColX and Col2 , suggesting a role for Ddr2 in regulating fibrillogenesis and extracellular matrix distribution.…”
Section: Molecular Regulation Of the Cranial Basementioning
confidence: 99%